Kisah Pemberantasan Bid’ah di Malaysia: Kajian atas Kitab Risalah Al-Azhari - Ali, Wan Zailan Kamaruddin Wan; Ismail, Ahmad Zuhdi (Hanifiya: Jurnal Studi Agama-Agama, 2019)
This article aims to study the idea and thought of Shaikh Muhammad Tahir Jalaluddin al-Falaki al-Azhari on the concept of bid’ah [innovation] dan the issues related to it. Bid’ah [innovation] is a problematic issue among muslim society in Malaysia. Generally, it is due to two main streams of thought between Kaum Muda [ultra-ortodox] and Kaum Tua [orthodox] that look at the issues from their own perspectives which are different from one another. In the context of this paper, it focuses to view the idea and thought of Shaikh Muhammad Tahir Jalaluddin himself. Hopefully, it will ease and help the muslim society in Malaysia to interact between them peacefully as allowed in Islam, and not vice-versa.